2022
DOI: 10.1136/bmjopen-2021-056478
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the adoption of health-promoting behaviours in patients with polycystic ovary syndrome: a cross-sectional study

Abstract: ObjectiveThis study aimed to investigate health-promoting lifestyle status and associated risk factors in patients with polycystic ovary syndrome (PCOS).DesignCross-sectional study.SettingThis study was conducted at a tertiary hospital in Guizhou, China from December 2020 to June 2021.ParticipantsA total of 366 participants (18–45 years) diagnosed with PCOS were recruited from the outpatient departments.MeasuresSociodemographic characteristics were collected, and health-promoting behaviours were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…The current findings, although reports that the respondents have adequate knowledge of the health-promoting behaviours, due to the anticipated inconsistencies in the practice of the same, the findings partially validate the reports of recent research such as Guo et al. (2022) that women in their early adulthood - reproductive age could have poor health-promoting behaviour.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The current findings, although reports that the respondents have adequate knowledge of the health-promoting behaviours, due to the anticipated inconsistencies in the practice of the same, the findings partially validate the reports of recent research such as Guo et al. (2022) that women in their early adulthood - reproductive age could have poor health-promoting behaviour.…”
Section: Resultssupporting
confidence: 87%
“…Hence, in the background of recent research, the current study could bring up the necessary bridge in enabling the individuals to practice what they know. Moreover, although the result of Guo et al. (2022) could resemble the Indian culture (due to the similarity of the collectivistic culture of China), further studies are warranted to explore the differences within the multicultural context of India.…”
Section: Resultsmentioning
confidence: 99%
“…The negative correlation between HL and BMI suggests that patients with high HL have healthier lifestyles [36]. Moreover, previous studies have suggested that a higher BMI is associated with poor health behaviors in the life management of patients with PCOS [21], which may explain the relationship between a high BMI and low HL. Furthermore, chronic disease prevalence increases with increasing BMI [37,38] and, since PCOS is a chronic disease and most patients are obese, this may also contribute to the negative relationship between HL and BMI.…”
Section: Discussionmentioning
confidence: 96%
“…The current study aims to affirm the role of SE in modulating psychological status and life management in PCOS [21,22]. However, existing research on the relationship between SE and QOL [21,22] has only identified a direct relationship through regression or correlation, and no study has explored this mediating relationship for patients with PCOS using structural equation modeling (SEM). SEM is a multivariate statistical framework used to model the complex relationships between directly and indirectly observed (latent) variables [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation